2020
DOI: 10.3390/cancers12082159
|View full text |Cite
|
Sign up to set email alerts
|

The Prowess of Andrographolide as a Natural Weapon in the War against Cancer

Abstract: There has been a paradigm shift in our understanding about the multifaceted nature of cancer and a wealth of information has revealed that single-target drugs are not good enough to provide satisfactory clinical outcomes and therapeutic effects for complex diseases which involve multiple factors. Therefore, there has been a reignition to search for natural products having premium pharmacological activities aim to efficiently target multiple deregulated cellular signaling pathways. Andrographolide, a diterpene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Andro possesses a remarkable inhibitory activity against inflammation, cancer, and viral infections ( Gupta et al, 2020 ). Current studies have revealed that it improves microcirculation and autophagy, while inhibits oxidative stress and cellular apoptotic process ( Yang et al, 2014 ; Geng et al, 2019 ; Farooqi et al, 2020 ; Li et al, 2020 ). However, there are few studies on Andro-induced autophagy especially in flap models.…”
Section: Discussionmentioning
confidence: 99%
“…Andro possesses a remarkable inhibitory activity against inflammation, cancer, and viral infections ( Gupta et al, 2020 ). Current studies have revealed that it improves microcirculation and autophagy, while inhibits oxidative stress and cellular apoptotic process ( Yang et al, 2014 ; Geng et al, 2019 ; Farooqi et al, 2020 ; Li et al, 2020 ). However, there are few studies on Andro-induced autophagy especially in flap models.…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide is a diterpene lactone isolated from Andrographis paniculata and inhibits the development of different types of cancer by regulation of Wnt/β-catenin, mTOR, VEGF-mediated intracellular signaling and TRAIL-mediated apoptosis [ 171 , 172 ]. Its MM inhibitory properties were investigated together with the sesquiterpene lactone parthenolide [ 159 ].…”
Section: Resultsmentioning
confidence: 99%
“…Factor -α (TNF -α) related Apoptosis inducing ligand (TRAIL -An important member of extrinsic apoptosis pathway) was significantly enhanced in various Human cancer 65 .…”
Section: Recent Work Demonstrates That Tumour Necrosismentioning
confidence: 99%